2004
DOI: 10.1037/0096-3445.133.3.339
|View full text |Cite
|
Sign up to set email alerts
|

Load Theory of Selective Attention and Cognitive Control.

Abstract: A load theory of attention in which distractor rejection depends on the level and type of load involved in current processing was tested. A series of experiments demonstrates that whereas high perceptual load reduces distractor interference, working memory load or dual-task coordination load increases distractor interference. These findings suggest 2 selective attention mechanisms: a perceptual selection mechanism serving to reduce distractor perception in situations of high perceptual load that exhaust percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

183
1,641
34
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,498 publications
(1,864 citation statements)
references
References 66 publications
183
1,641
34
6
Order By: Relevance
“…One randomly-determined block was the high WM load block. Participants were presented with six digits for two seconds before each vignette; following the comprehension question, participants were presented with a single digit, and were asked to indicate with a key-press whether they saw this digit before the vignette (new foil digits were presented on 50% of trials, see Lavie et al, 2004). The low WM load block was identical except that only one digit was presented before each vignette.…”
Section: Did You Stand Up To Speak? (Yes/no)mentioning
confidence: 99%
“…One randomly-determined block was the high WM load block. Participants were presented with six digits for two seconds before each vignette; following the comprehension question, participants were presented with a single digit, and were asked to indicate with a key-press whether they saw this digit before the vignette (new foil digits were presented on 50% of trials, see Lavie et al, 2004). The low WM load block was identical except that only one digit was presented before each vignette.…”
Section: Did You Stand Up To Speak? (Yes/no)mentioning
confidence: 99%
“…We could thus, within a Bayesian framework, characterize the brain connectivity of the two groups of subjects, as well as their differences. We hypothesized that controls would display a connectivity network compatible with the Load Theory (Lavie et al, 2004) with a reduced drive of the activity in V4 in high attentional load mediated either by a direct action of P on V4 or by an indirect decrease of the gating from V1 to V4 (Schwartz et al, 2005;Stephan et al, 2008). We hypothesized that the connectivity of this visuo-attentional system would differ between MDD and controls in two distinct ways.…”
Section: Introductionmentioning
confidence: 98%
“…Neuroimaging studies showed that these symptoms are mainly associated with impairments within fronto-limbic network involved in affective regulation and fronto-parietal networks involved in attention and executive functions (Mayberg et al, 1999). Lavie et al (2004Lavie et al ( , 2005 proposed the 'Load Theory' of attention in which distractor rejection depends on the level and type of attentional load involved by the current task. This theory of attention and cognitive control implies reciprocal interactions for the processing of taskrelevant and task-irrelevant information.…”
Section: Introductionmentioning
confidence: 99%
“…The salient study context "assessment of sexual attractiveness" could have encouraged homophobic behavior of male participants (Jellison, McConell, & Gabriel, 2004). It should be noted that these regulatory mechanisms might have required cognitive resources (Lavie, Hirst, Fockert, & Viding, 2004), so that task monitoring and performance could have been compounded. This might have been a reason for men's comparatively high prosaccadic error rates while viewing male stimuli.…”
Section: Prosaccadic Results Of Menmentioning
confidence: 99%